2023
DOI: 10.3390/antiox12071336
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Carotenoids and Polyphenols and Their Association with MetS: The Need for Nutritional Interventions

Abstract: Metabolic syndrome (MetS) is characterized by increased pro-oxidative stress and a chronic inflammation state and their consequent alterations. Several studies have highlighted the protective effect of carotenoids and polyphenols in MetS patients. This study aimed to evaluate the plasma level of selected carotenoids and polyphenols and to determine their relationship with MetS severity, MetS components, and inflammatory markers in Polish adults with metabolic disorders. It was designed as a cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…Similar results were presented by Matsumoto et al [71], indicating that higher levels of lutein and β-carotene in serum were only associated with lower levels of visceral fat area in women, while the observed positive correlation between lycopene and visceral fat (in men) could be explained by the low level of dietary intake and the influence of other nutrients in dishes. Plasma levels of most carotenoids were inversely correlated with fat mass and general and central obesity [61,72], and with weight loss, serum lutein, and zeaxanthin concentrations increase [23]. This is also corroborated by our results, where the increase in plasma lutein concentration during the weight loss program was higher than that of β-carotene and lycopene.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were presented by Matsumoto et al [71], indicating that higher levels of lutein and β-carotene in serum were only associated with lower levels of visceral fat area in women, while the observed positive correlation between lycopene and visceral fat (in men) could be explained by the low level of dietary intake and the influence of other nutrients in dishes. Plasma levels of most carotenoids were inversely correlated with fat mass and general and central obesity [61,72], and with weight loss, serum lutein, and zeaxanthin concentrations increase [23]. This is also corroborated by our results, where the increase in plasma lutein concentration during the weight loss program was higher than that of β-carotene and lycopene.…”
Section: Discussionsupporting
confidence: 88%
“…Carotenoids are a class of lipophilic pigments that are primarily present in vegetables and fruits, which cannot be synthesized by humans and must be obtained from dietary intake. Carotenoids have antioxidant, antibacterial, immunomodulatory, and anti-inflammatory activities, as well as the potential to reduce markers associated with metabolic syndrome 61 . Another prospective study from China explored the relationship between serum carotenoids and NAFLD in middle-aged and older adults and indicated that higher concentrations of serum carotenoids may improve NAFLD by reducing inflammation, insulin resistance, triglycerides, and BMI 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids are a class of lipophilic pigments that are primarily present in vegetables and fruits, which cannot be synthesized by humans and must be obtained from dietary intake. Carotenoids have antioxidant, antibacterial, immunomodulatory, and antiinflammatory activities, as well as the potential to reduce markers associated with metabolic syndrome 61 62 . In addition, oral supplementation with vitamin C may also improve liver function and glucose in patients with NAFLD, especially 1000 mg/day, and these findings are consistent with our research results 63 .…”
Section: Discussionmentioning
confidence: 99%
“…This has been a way of reducing the potential bias from dietary questionnaire-based data. While the evidence on the determination of plasma (poly)phenols is not extensive, a recent review described the common analytical technique utilizing LC-MS/MS [53]. However, the use of differential isotope labelling in our methodology is an extra advantage.…”
Section: Plasma (Poly)phenols and Weight Change In Epicmentioning
confidence: 99%